2023
DOI: 10.2147/cia.s383609
|View full text |Cite
|
Sign up to set email alerts
|

Combination of the Barthel Index at Discharge with GRACE Leads to Improved One-Year Mortality Prediction in Older Patients with Acute Myocardial Infarction

Abstract: Purpose Many older patients with acute myocardial infarction (AMI) have impaired ability for activities of daily living (ADL). Impaired ADL leads to poor prognosis in elderly patients. The Global Registry of Acute Coronary Events (GRACE) score is widely used for risk stratification in AMI patients but does not consider physical performance, which is an important prognosis predictor for older adults. This study assessed whether the Barthel Index (BI) score combine the GRACE score would achieve impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…It is widely acknowledged that higher ADL scores are strongly associated with better outcomes and fewer complications [ 35 ]. Impaired ADL has not only been associated with the incidence of cardiovascular diseases, such as heart failure and ACS, but also has been recognized as a prognostic factor for complications and long-term mortality in patients with these cardiovascular diseases [ 20 , 30 ]. This study found impaired ADL was an independent risk factor for periprocedural myocardial infarction and injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely acknowledged that higher ADL scores are strongly associated with better outcomes and fewer complications [ 35 ]. Impaired ADL has not only been associated with the incidence of cardiovascular diseases, such as heart failure and ACS, but also has been recognized as a prognostic factor for complications and long-term mortality in patients with these cardiovascular diseases [ 20 , 30 ]. This study found impaired ADL was an independent risk factor for periprocedural myocardial infarction and injury.…”
Section: Discussionmentioning
confidence: 99%
“…A 2-year follow-up study revealed that ADL assessment at hospital admission could be used for risk assessment in patients with acute coronary syndrome (ACS) and long-term treatment planning [ 19 ]. Another recent study demonstrated that ADL assessment at discharge was an independent risk factor for mortality in patients with acute myocardial infarction (AMI) [ 20 ]. However, the association between ADL and short-term complications of cardiovascular disease has not been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%